Neoliberalismo e hegemonia burguesa: ação social empresarial através dos Institutos Ethos de Responsabilidade Social Empresarial e Empresas e Gife (Grupos de Institutos, Fundações e Empresas) - Andrade, Luana Maria de [UNESP] (2014)
In this dissertation, we analyze the strategies , discourses and actions of the Institutes Gife and Ethos to the social sphere . For this purpose, the analysis is focused on reasons why these two organizations of such magnitude, Gife and Ethos has been created in Brazil aiming at a distinct social entrepreneurs role associated to traditional philanthropy and welfare performed up to then. With this goal, have been analyzed both the historical conditions and key actors that made possible the raising of a new business activity expressed in the ideology of CSR and Private Social Investment policies. Thereto, due the 1980s political opening, entrepreneurs or fractions of the capitalists was forced to redefine their strategies of domination. They could not have the coercion as predominant element, requiring strategies to more consensual nature new political arrangements in this political framework. With the implementation of neoliberalism in the country, the social activism of entrepreneurs began gaining prominence and strength, since the state policy for the social area developed, particularly in the 1990s, through the shrinkage of state liability against social problems, allowing for the intervention of the private sector in this area . In this scenario, were created the institutions considered in this research as the main organizers and formulators of the new social entrepreneurial action. These organization acting as private apparatus of hegemony seeking to spread a new political perspective grounded in the tenets of neoliberalism applied to political and economic problems, attributing other meanings to how these problems should be treated.